Unveiling the key drivers of effective e-procurement in local government: a mixed-method analysis - Prasetyo, Deddy; Ambarwati, Rita (BISMA (Bisnis dan Manajemen), 2025)
Electronic procurement (e-procurement) based on e-procurement quality dimensions. In this unique case, the realisation of electronically conducted procurement has shown a declining trend over the past five years. Adopting a mixed-methods approach that combines qualitative interviews and quantitative surveys with 200 respondents, this research analyses the quality dimensions of e-procurement services and their effects on procurement outcomes. Data processing was carried out using the SPSS Version 29.0 software application, starting from validity, reliability and factor analysis tests. The findings reveal a new variable as a factor influencing the performance and quality of e-procurement, namely the regulatory variable. The results of the factor analysis tests indicate that regulatory factors, with variable indicators, include regulations that support the integration of electronic procurement with the financial system, laws that enable the formulation of price standards relevant to e-catalogues, and regulations that facilitate the development of price standards. Training is also a strategic issue that has been found to have a significant influence on the quality. The implication is that users, in this case, must pay attention to the formation of the first factor, especially to the training and regulation factors.